Digital Reading Platforms in ELT: A Global Review of Practices and Impacts (2015-2025) - Annisa Fadillah; Salasiah Ammade (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2025)
The goal of this study is to present a thorough worldwide summary of how digital reading platforms have been incorporated into English language teaching (ELT) throughout the 2015–2025 timeframe. Platforms such as Epic!, ReadWorks, Raz-Kids, and M-Reader have had a significant impact on how reading is taught, practiced, and assessed in English as a Foreign Language (EFL) and English as a Second Language (ESL) contexts due to the growing role of digital technologies in education, particularly during the COVID-19 pandemic. This study examined academic publications indexed in Scopus, Web of Science, Google Scholar, and the Connected Papers platform using a qualitative methodology and a systematic literature review strategy. Four main themes emerged from the review and classification of the articles: the difficulties, types, impacts, and efficacy of digital reading platforms. Research indicates that while digital platforms offer benefits including enhanced motivation, tailored learning, accessibility, and engagement, they also present challenges. These include issues related to privacy and data justice, multimedia distractions, the digital divide, and inadequate teacher preparation. Additionally, it has been demonstrated that digital technologies affect students’ digital identities, instructor autonomy, and institutional frameworks. According to the study’s findings, pedagogical integration and the broader educational ecosystem are just as important to the efficacy of digital reading platforms as the technology itself. In order to ensure the ethical and effective use of digital technologies in ELT globally, the review emphasizes the necessity of critical implementation, contextual adaptation, and multidisciplinary cooperation.